2014
DOI: 10.7727/wimj.2013.273
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effects of Cocoa Consumption on Blood Pressure

Abstract: Hypertension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
0
10
0
3
Order By: Relevance
“…The short-term blood pressure changes to a single drink of designated dose of cocoa was found to be statistically significant (4). The authors of the study group observed maximum decreases in both systolic and diastolic pressure up to 20 mmHg.…”
Section: Kk Hoementioning
confidence: 85%
“…The short-term blood pressure changes to a single drink of designated dose of cocoa was found to be statistically significant (4). The authors of the study group observed maximum decreases in both systolic and diastolic pressure up to 20 mmHg.…”
Section: Kk Hoementioning
confidence: 85%
“…Although concerns regarding the bioavailability and the extent to which phenols are biologically active have not been completely clarified, numerous capabilities have been assigned to cocoa flavonoids. Several studies analyzing the biological properties of these molecules have provided considerable supportive evidence of flavonoid’s role in improving vascular functions, preventing related endothelial dysfunctions and diseases, reducing insulin-resistance indices , (probably as a result of a decrease in insulin secretion), increasing insulin-sensitivity, , contributing to anti-inflammatory reactions, inhibiting platelet aggregation and activation, and decreasing blood pressure. ,, However, a meta-analysis of randomized trials does not confirm the flavonoid effect on systolic blood pressure, whereas a second meta-analysis has found a small but statistically significant effect in lowering systolic and diastolic blood pressure in the short term . Multiple trials have emphasized that cocoa has the ability to change the lipid fraction not only by limiting its oxidation but also by directly altering the lipid profile of plasma, increasing high-density lipoprotein (HDL) and reducing LDL , , and total cholesterol .…”
Section: Other Constituents Of Cocoa and Chocolate: Quantity And Effe...mentioning
confidence: 99%
“…Além dos nutrientes essenciais, as frutas e hortaliças, por exemplo, são constituídas por compostos químicos que podem gerar diversos benefícios à saúde humana, chamados de compostos bioativos. (ALEYNE, et al, 2014) Nesse sentido, há uma maior demanda por alimentos que cumprem suas funções básicas, mas que também ofereçam benefícios à saúde, ou seja, alimento funcionais.…”
Section: Introductionunclassified